Desarrollo profesional hacia el dominio del sistema SAP - Seminario Silvera, Franklin Said (2023)
The systems engineer from the University of Lima is a professional who plays a key role in organizations thanks to his technical capabilities and knowledge of the Company operation that enables him to propose, evaluate, develop and implement information technology solutions. During my professional performance important achievements have been achieved, I mention: Technically lead integration projects with SAP that guarantee tangible benefits to the business. Implement improvements in SAP that facilitate the day-to-day of collaborators. Increase the satisfaction level of companies with the SAP support and maintenance service. In recognition, I have carried out a career line in the company Productos Tissue del Peru S.A.C, where I started as a SAP Analyst, I was promoted to SAP Specialist and I currently work as a SAP coordinator. Undoubtedly, the achievements and recognitions obtained would not have been possible without a comprehensive development, in the contents: Technical capacity to apply functional and technical knowledge in solutions for the digital transformation of companies. Management capacity to apply creativity and social skills such as effective communication, leadership, negotiation skills and teamwork in solving problems and conflicts. Continuous learning to be at the forefront of SAP technology trends. Ethical conduct for the exercise of the profession in a dignified and fair manner. As lessons learned from my professional experience, I consider it vital to plan the scope of a solution before the activities to prevent project teams from wasting time and resources solving problems beyond their competence. Additionally, in the face of failures or mistakes, drawing conclusions to facilitate learning is crucial.